2017
DOI: 10.1123/tsp.2016-0081
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Preperformance Psychobiosocial States with Music

Abstract: The purpose of the study was to investigate the effects of music on swimmers’ preperformance psychobiosocial states. A purposeful sample of competitive swimmers (N = 17) participated in a 5-week intervention grounded in the individual zones of optimal functioning (IZOF) model. Findings showed that (a) preperformance psychobiosocial states differentiated between best and worst performances, (b) swimmers improved their ability to regulate preperformance states through the use of music, and (c) the use of music h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The research and applied advantages of assessing psychobiosocial states using either idiographic or nomothetic methods have been demonstrated in many studies conducted both in sport (e.g., Bortoli et al, 2009Bortoli et al, , 2011Bortoli et al, , 2012Middleton et al, 2017;Morano et al, 2020;Nateri et al, 2020;Ruiz & Hanin, 2004a, 2004bRuiz et al, 2019a) and physical education contexts (e.g., Bortoli et al, 2014Bortoli et al, , 2015Bortoli et al, , 2017Di Battista et al, 2019). For example, a state-like assessment was implemented within 1 hr prior to competition on elite basketball players and carom billiard players using a nomothetic method (i.e., same lists of functional and dysfunctional states across athletes).…”
Section: Differential Scalementioning
confidence: 99%
“…The research and applied advantages of assessing psychobiosocial states using either idiographic or nomothetic methods have been demonstrated in many studies conducted both in sport (e.g., Bortoli et al, 2009Bortoli et al, , 2011Bortoli et al, , 2012Middleton et al, 2017;Morano et al, 2020;Nateri et al, 2020;Ruiz & Hanin, 2004a, 2004bRuiz et al, 2019a) and physical education contexts (e.g., Bortoli et al, 2014Bortoli et al, , 2015Bortoli et al, , 2017Di Battista et al, 2019). For example, a state-like assessment was implemented within 1 hr prior to competition on elite basketball players and carom billiard players using a nomothetic method (i.e., same lists of functional and dysfunctional states across athletes).…”
Section: Differential Scalementioning
confidence: 99%
“…In terms of evaluating research rigour, some researchers addressed integrative quality criteria that they framed as applicable to the study as a whole (e.g., Karageorghis et al, 2018;Mallinson-Howard et al, 2018;Rumbold et al, 2018;Thrower et al, 2019), but more often quantitative and qualitative parts of the study were evaluated separately (e.g., Kacperski & Hall, 2017;Middleton et al, 2017;Redwood-Brown et al, 2018;Richard et al, 2017;Whitehead et al, 2018). From the integrative perspective, Thrower et al (2019) suggested that "taken as a whole, this study can be judged on the capacity to which it is relevant for the research questions, is transparent, has a rationale for using mixed methods, and requires the integration of mixed-method findings", while at the same time maintaining that "the quality criteria for each aspect of the study should be considered separately" (p. 4).…”
Section: Considerations Of Research Qualitymentioning
confidence: 99%
“…However, though these approaches do not seek to change the content of athletes’ experiences [ 19 ], self-regulation involves deliberate behaviors aimed to down-regulate dysfunctional experiences, or up-regulate or maintain functional experiences [ 9 ]. Some of the strategies that athletes can use to regulate their emotions include relaxation (e.g., focus on breathing), imagery [ 20 ], music [ 21 , 22 ], or mindfulness–acceptance-based approaches [ 23 ]. Based on these self-regulation strategies the athletes often use spontaneously, during the intervention, we combined somatic techniques (i.e., paced breathing and relaxation) and mental imagery of challenging competitive situations to help players experience and mentally strengthen the optimal conditions for performance.…”
Section: Introductionmentioning
confidence: 99%